A CRITICAL EDITION OF A MANUSCRIPT CHIKITSA SARA BY GOPALADASA TO KNOW ITS CONTRIBUTIONS. - 1. Dr. Vidyarani. K.P , 2. Dr. Shrinath. M. Vaidya (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Ayurveda manuscripts are the intellectual wealth of India1 and considered one of the main knowledge resources of human kind. This study is based on critical edition of the manuscript CHIKITSA SARA to update and conserve the knowledge present in it, which was in the form of manuscript at Gujarat Ayurveda Manuscript library, Jamnagar. The text cikits¡ s¡ra was authored by Gopaladasa and by considering the internal and external evidences the time period of the author is estimated as early 16th century AD. The text deals with six branches among ashtangas of Ayurveda (except Rasayana and Vajikarana). It is the compilation from various texts such as Caraka, Sushruta, Vagbhata, Rasarnava, Harita, and Atreya Samhita as mentioned in the text by the author. Generally, the trisutra form i.e. hetu, linga and oushadha has been followed with brief description of samprapti, lakshana and chikitsa sutra. More detailed description of medicinal formulations and also, about the ahara varga and gunas of Kashtoushadhis are dealt in the text.